Effect of anti-obesity agent HSG4112 on overweight and obese patients following 12 weeks of oral treatment: a study protocol for a randomised, double-blind, placebo-controlled, parallel-group, phase 2a clinical trial - Kyungha Min; Bumjo Oh; Hye Yeon Koo; Yang-Hyun Kim; Ji-Won Lee; Ji-Won Lee; Sangsub Lee; Youngah Kim; Hyuktae Kwon (Frontiers Media S.A., 2023)
Background: Glaceum Inc. has proposed HSG4112, a structural analogue of glabridin, as a novel anti-obesity compound. Animal studies and phase I human trials have shown that HSG4112 improves energy consumption, normalises weight, and is safe and drug-resistant. Based on these results, the company plans to conduct a phase 2a clinical trial to determine the safety and efficacy of HSG4112 in overweight and obese patients. Methods: A 16-week randomised, double-blind, placebo-controlled, parallel-group trial will be conducted at five large hospitals in South Korea to assess the safety and efficacy of HSG4112 in overweight and obese patients. Participants who meet the inclusion/exclusion criteria will be assigned a subject number and randomly assigned to one of the four treatment groups (one group receiving a placebo) in a 1:1:1:1 ratio. The study's primary outcome will be to monitor the change in body weight (kg) from baseline to the end of treatment while monitoring safety and tolerability. Discussion: This trial will evaluate the efficacy and safety of HSG4112 in overweight and obese adults. Upon proving the safety and effectiveness of the newly developed mechanism, it might significantly improve the perception of the product among medical personnel and obese patients. Furthermore, it may aid in managing chronic conditions that require long-term treatment.Trial registration:ClinicalTrials.gov, identifier [NCT05197556].